Zum Verhältnis von Unterlassungsanspruch und Rückrufanspruch - Klinger, Cornelius (Tectum Verlag, 2023)
It is generally accepted that the injured party must act to comply with the injunction if inaction would be tantamount to a continuation of the infringing act. It is controversial whether the injured party is also obliged to cease acts that affect the sphere of independent third parties. The author examines whether an extension of the injunction to a recall obligation is necessary to ensure effective legal protection from the creditor's point of view. Furthermore, it is examined whether the extension of the injunctive relief is accompanied by an increase in efficiency. In addition, the specific recall obligation of the injunction debtor in different distribution constellations is determined.